2017
DOI: 10.5740/jaoacint.17-0001
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Eco-Friendly Liquid Chromatographic and Spectrophotometric Methods for Simultaneous Determination of Coformulated Drugs: Phenylephrine Hydrochloride and Prednisolone Acetate

Abstract: Five simple, sensitive, and eco-friendly LC and UV spectrophotometric methods have been developed for the simultaneous determination of phenylephrine hydrochloride (PHE) and prednisolone acetate (PRD) in their combined dosage form. The first method was reversed-phase (RP) LC using methanol-water-heptane-1-sulfonic acid sodium salt (75 + 25 + 0.1, v/v/w) as a mobile phase. Separation was achieved using an XSelect HSS reversed-phase C18 analytical column (250 × 4.6 mm, 5µm). The flow rate was 1.0 mL/min and UV d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Our main motive was to phase out the usage of toxic chemicals associated with conventional analytical methods without compromising the efficacy of the analytical procedure. Consequently, efforts are being exerted to find various analytical methods that don't require consumption of hazardous solvents [46,47]. More-over, various approaches can be used to assess the greenness of the method.…”
Section: Greenness Assessment Of the Proposed Potentiometric Method: Analytical Eco-scalementioning
confidence: 99%
“…Our main motive was to phase out the usage of toxic chemicals associated with conventional analytical methods without compromising the efficacy of the analytical procedure. Consequently, efforts are being exerted to find various analytical methods that don't require consumption of hazardous solvents [46,47]. More-over, various approaches can be used to assess the greenness of the method.…”
Section: Greenness Assessment Of the Proposed Potentiometric Method: Analytical Eco-scalementioning
confidence: 99%
“…Review of literature revealed several methods for PHE estimation in combination with some other drugs, including UV-spectrophotometric method. [5][6][7] Purity assessment of ebastine and PHE by Ultra-Performance Liquid Chromatography (UPLC), 8 assay of PHE and diphenhydramine oral solutions using Ultra-High-Performance Liquid Chromatographic (UHPLC), 9 simultaneous estimation of ascorbic acid, PHE, paracetamol and levocetirizine hydrochloride by RP-HPLC. 10 HPLC-diode array detection technique for estimating phenylephrine hydrochloride, dimetindene maleate, and benzalkonium chloride simultaneously, 11 estimation of cetirizine along with PHE in tablet by RP-HPLC method, 12 PHE with acetaminophen, dextromethorphan, doxylamine, guaifenesin, caffeine and aspirin in various cold and cough formulations by RP-HPLC, 13 cyclopentolate hydrochloride and PHE determination in presence of their potential degradation by HPLC, 14 simultaneous determination and impurity-profiling of ebastine and phenylephrine hydrochloride by HPTLC (High-Performance Thin-Layer Chromatography), 15 analysis of ketorolac tromethamine, PHE and chlorpheniramine maleate in ternary mixture using HPTLC 16 and HPTLC determination of paracetamol, PHE, caffeine and chlorpheniramine in the tablet S799 Srivastava, et al: Forced Degradation Studies of Phenylephrine by RP-HPLC have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…1 [4][5] . A detailed investigation revealed that analytical methods exist for estimating specified drugs with other combinatorial by RP-HPLC [6][7][8][9][10][11][12][13][14][15][16] . There were few RP-HPLC methods for the estimation of DMP, PHE, and TPN simultaneously, for specified combination in solid dosage form 17 and for combined liquid dosage form 18 .…”
mentioning
confidence: 99%